Edukasi Pentingnya Menjaga Kesehatan Reproduksi Pada Anak Remaja Di SMA Angkasa 1 Lanud Medan - Ningrum Wahyuni; Wan Tisya Muhaira; Hendri Meirialdi; Januarisman Andrian Saragih; Widia Maulida (CV. Devi Tara Innovations, 2024)
Adolescence is one of the periods of human development. This is a time of change or transition from childhood to adulthood that includes biological, psychological, and social changes. Adolescence usually begins at the age of 10 – 13 years and ends at the age of 18 – 22 years. Meanwhile, according to WHO, adolescents are individuals who are experiencing a transition period that gradually reaches sexual maturity, experiences a change in the psyche from a child's soul to an adult, and experiences a change in economic circumstances from dependence to relative independence. There are two main aspects of change in adolescents, namely physical or biological changes and psychological changes. Many problems will arise as a result of neglecting reproductive health. Problems that arise due to lack of knowledge about reproductive health are Unwanted Pregnancy (KTD), abortion, early marriage and marriage, STIs or STDs and HIV/AIDS (Marmi, 2013). One of the efforts that can be made to reduce these numbers is by conducting health education about how to care for reproductive organs, education about adolescent development during puberty, health education about the impact of pornography, health education about unwanted pregnancies (KTD) and abortion, health education about HIV/AIDS and sexually transmitted infections, and health education about maturing the age of marriage with involving the role of the government, parents, and also peer groups. By carrying out these activities, it is hoped that it will be able to increase the knowledge of adolescents, so that it can increase adolescents' awareness of the importance of reproductive health problems. And reduce the incidence of adolescent reproductive health cases.